Behind the screens : an investigation on self-disclosure behavior on Instagram - Lien, Dylan Tong Li (Nanyang Technological University, 2020)
Instagram is an image-based social networking site that has gained increasing popularity over the past couple years, especially amongst young adults. Given how social networking sites have intertwined and become a regular part of our everyday lives, it is important to understand how individuals are affected by its use. Before we can explore these effects, however, we must first understand the way individuals behave on these platforms, such as through their self-disclosures. However, existing research has yet to fully establish such behaviors in the context of social networking sites, let alone newer ones like Instagram. With the aim to investigate the relationships between self-esteem, orientation to happiness, and intensity of Instagram use, in the context of online self-disclosure on Instagram, the present study hypothesized a positive correlation between both self-esteem and orientation to happiness, and online self-disclosure on Instagram, as well as a potential moderating role of intensity. The present study demonstrated that self-esteem was generally positively related to online self-disclosure on Instagram, while orientation to happiness was generally not. Additionally, Instagram intensity was found to be a moderator for select relationships between self-esteem and orientation to happiness, and the dimensions of online self- disclosure on Instagram.